TEOLOGI MAGISTERIUM DAN KONSERVATISME GEREJA: SEBUAH STUDI ATAS AJARAN KONTRASEPSI - Sudarto, Tulus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2006)
There has been a significant change in the Church as a communio since the secondVatican Council ( 1962-1965). The Council seemed to instigate a mode of doing theology with liberal overtone. New ways of looking at things had been shown quite impressively by the Church ever since. Indeed “Ecclesia semper reformanda”. This, however, is not the whole story, for in the case like contraception, and worse still, on magisterium in general, it turns out that the Church hardly changes. The dilemma has brought about many problems,practically as well as theologically. This article talks about the dilemma.